The value of biodiversity in economic decision making: Applying the IEEM+ESM approach to conservation strategies in Colombia - Onil Banerjee; Martín Cicowiez; Žiga Malek; Peter Verburg; Renato Vargas; Sean Goodwin (Inter-American Development Bank (IDB), 2020)
In this paper we evaluate the economic, natural capital and ecosystem services impacts of strategies for conserving Colombias rich natural capital endowment. Specifically, we consider Government program proposals for establishing Payment for Ecosystem Services (PES), implementing more sustainable silvopastoral systems and expanding habitat banking. We develop and apply the Integrated Economic-Environmental Modeling (IEEM) Platform linked with spatial Land Use Land Cover (LULC) and Ecosystem Services Modeling (IEEMESM) to shed light on the multi-dimensional impacts of these programs from the perspective of sustainable economic development and intergenerational wealth. Advancing the state-of-the-art in integrated economic-environmental modeling, our framework for the first time integrates dynamic endogenous feedbacks between natural capital, ecosystem services and the economic system to fully capture how changes in natural capital and ecosystem service flows affect the economy and vice versa. Our approach quantitatively models the economy, natural capital and ecosystem services as one integrated and complex system at a high level of spatial resolution across Colombias 32 Departments. [...]
Keywords: C68; E21; Q15; Q2; Q5; 330; Integrated Economic-Environmental Modeling (IEEM) Platform; dynamic computable general equilibrium (CGE) model; ecosystem services modeling; land use land cover modeling; natural capital; payment for ecosystem services; habitat banking; Colombia